Analisis Faktor-Faktor Yang Mempengaruhi Hasil Belajar Pada Tema 1 Subtema 1 Semester Gasal Di Kelas IV SD Negeri Kembanglangit Tahun Ajaran 2021/2022 - Ricky Setya Wijaya; Mudzanatun Mudzanatun; Asep Ardiyanto (STKIP Andi Matappa Pangkep, 2022)
This research is motivated by the decline in learning outcomes of 4th grade students at SD Negeri Kembanglangit. This is because there are factors that affect the learning outcomes of grade 4 students. Of course, teachers must immediately take action and find solutions so that the learning outcomes of grade 4 students at SD Negeri Kembanglangit increase. This study aims to determine what factors affect learning outcomes along with solutions to overcome these problems. This study uses qualitative research by describing facts from data sources obtained through observation, interviews, questionnaires and documentation. The final results of this study indicate that some of these factors are the lack of focus of students when learning is in progress, lack of interest of students in certain subjects, students rarely study at home and student assignments that are often done by their parents. Suggestions from researchers are that students are expected to be more motivated when studying, parents of students should also accompany children when studying at home. In addition, students also have to do their own homework, the goal is for students to learn and become accustomed to dealing with questions.